Crystallization and preliminary X-ray analysis of crinumin, a chymotrypsin-like glycosylated serine protease with thrombolytic and antiplatelet activity - Singh, Kunwar Awaneesh (International Union of Crystallography, 2011)
Crinumin, a novel glycosylated serine protease with chymotrypsin-like catalytic specificity, was purified from the medicinally important plant Crinum asiaticum. Crinumin is a 67.7 kDa protease with an extraordinary stability and activity over a wide range of pH and temperature and is functional in aqueous, organic and chaotropic solutions. The purified protease has thrombolytic and antiplatelet activity. The use of C. asiaticum extracts has also been reported for the treatment of a variety of disorders such as injury, joint inflammation and arthritis. In order to understand its structure–function relationship, the enzyme was purified from the plant latex and crystallized by the hanging-drop vapour-diffusion method. X-ray diffraction data were collected from a single crystal and processed to 2.8 Å resolution. The crystal belonged to the monoclinic space group C2, with unit-cell parameters a = 121.61, b = 95.00, c = 72.10 Å, α = γ = 90, β = 114.19°. The Matthews coefficient was 2.81 Å(3) Da(−1), corresponding to a solvent content of 56%, assuming one molecule in the asymmetric unit. Structure determination of the enzyme is in progress.